Unforeseen challenges to global health system, in particular context to COVID-19 pandemic and health care personnel. Issue 1 (1st January 2021) - Arshid, Muhammad Awais; Mumtaz, Maha; Nazir, Rashid
Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease which has spread throughout the world in a matter of approximately three months only. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and is the causative agent of a very fatal disease that has had global implications, in healthcare, medical resources and the financial economies. The SARS-CoV-2 has been suggested to have a zoonotic origin, based on the reports of the virus originating from the animal market in Wuhan, China. The disease is spread amongst humans via direct contact and respiratory droplets. The virus mainly infects the respiratory system and also involves other major organ systems. As this is a novel coronavirus, there has not been many studies regarding the virus's infectivity and treatment. However, since its emergence, efforts have been made to differentiate it from other diseases having a similar presentation, for treatment and for production of a vaccine. In this manuscript, we aim to highlight the important traits of the novel coronavirus, the disease COVID-19 and its presentation. The particular focus is based on the effects of COVID-19 on human health and its available therapeutic measure. At the time of this pandemic, the global health systems were not adequately sufficed to appropriately deal with it. Most importantly, and unfortunately, the health care personnel and their health is being largely overlooked during the COVID-19 pandemic. The manuscript is, therefore, an effort to draw the world's attention towards the role of health care workers, the problems they are facing as the frontline soldiers in this unforeseen battlefield and their sustenance during this COVID-19 pandemic situation. The doctors, nurses and other paramedical staff is dealing the COVID-19 suspects and patients on daily basis with merely available precautionary measures across the globe, consequently putting their lives and wellbeing on risks for the sake of humanity. And, with the support of scientific literature and other reliable resources, we aimed with this viewpoint manuscript to highlight the COVID-19 related challenges to global health system, in particular context to health care personnel.